Impact of neoadjuvant relugolix on patient-reported sexual function and bother - Hsueh, Jessica Y.; Gallagher, Lindsey; Koh, Min Ji; Eden, Shaine; Shah, Sarthak; Wells, Markus; Danner, Malika; Zwart, Alan; Ayoob, Marilyn; Kumar, Deepak; Leger, Paul; Dawson, Nancy A.; et al. (Frontiers in Oncology, 2024)
Introduction Sexual function following local treatment for prostate cancer is an important quality of life concern. Relugolix is a novel oral GnRH receptor antagonist used in combination with radiation therapy in the treatment of unfavorable prostate cancer. It has been shown to achieve rapid and profound testosterone suppression. As a result, these very low testosterone levels may impact both sexual functioning and perceptions. This prospective study sought to assess neoadjuvant relugolix-induced sexual dysfunction prior to stereotactic body radiation therapy (SBRT). Methods Between March 2021 and September 2023, 87 patients with localized prostate cancer were treated with neoadjuvant relugolix followed by SBRT per an institutional protocol. Sexual function and bother were assessed via the sexual domain of the validated Expanded Prostate Index Composite (EPIC-26) survey. Responses were collected for each patient at pre-treatment baseline and after several months of relugolix. A Utilization of Sexual Medications/Devices questionnaire was administered at the same time points to assess erectile aid usage. Results The median age was 72 years and 43% of patients were non-white. The median baseline Sexual Health Inventory for Men (SHIM) score was 13 and 41.7% of patients utilized sexual aids prior to relugolix. Patients initiated relugolix at a median of 4.5 months (2-14 months) prior to SBRT. 95% and 87% of patients achieved effective castration (≤ 50 ng/dL) and profound castration (< 20 ng/dl) at SBRT initiation, respectively. Ability to have an erection, ability to reach orgasm, quality of erections, frequency of erections, and overall sexual function significantly declined following relugolix. There was a non- significant increase in sexual bother. Discussion In concordance with known side effects of androgen deprivation therapy (ADT), neoadjuvant relugolix was associated with a significant decline in self-reported sexual function. However, patients indicated only a minimal and non-significant increase in bother. Future investigations should compare outcomes while on relugolix directly to GnRH agonist-induced sexual dysfunction.